Political and Gender issues in Arundhati Roy’s "The Ministry of Utmost Happiness" - Danish Suleman; Abdul Halim Mohamed; Md. Firoj Ahmmed (Indonesian Journal of Cultural and Community Development, 2020)
Arundhati Rao is an acute observer of the very fabric of Indian society. He is an activist and social reformer for the marginal, downtrodden and a revolutionary spark for the 21st century litterateurs. The Ministry of Utmost Happiness is the second novel of Booker Prize-winning author Arundhati Roy which is published in 2017 after twenty years of the publication of his debut novel The God of Small Things. The novel recounts some of the egregious events of Contemporary Indian history such as land reform, 2002 Godhra train burning and Kashmir insurgency as well. It illustrates the sufferings, pain and the right of the LGBT community in contemporary India. The novel also incorporates many social and political events occurred in India and other parts of the world against the backdrop of its story. The paper argues upon the political and gender issues with the reference of The Ministry of Utmost Happiness by Arundhati Rao.